In vitro and in vivo activity of the essential oil and nanoemulsion of Cymbopogon flexuosus against Trichomonas gallinae - Bruna Baccega; Yan Islabão; Alexia Mello; Filipe Martins; Carolina Santos; Aline Ourique; Samanta Gundel; Marcia Macedo; Élvia Vianna; Nara Farias; Camila Oliveira (Mashhad University of Medical Sciences, 2021)
Objective: This study was done to evaluate the in vitro and in vivo effects of the essential oil (OE-CL) and nanoemulsion (N-CL) of Cymbopogon flexuosus against Trichomonas gallinae. Materials and Methods: In vitro assays were done with 106 parasites and OE-CL and N-CL in the concentrations: 110, 220, 330, 440, 550, 660, 770 and 880 µg/ml and four controls: CN (culture medium and trophozoites), MTZ (trophozoites plus 800 µg/ml of metronidazole), TW (trophozoites plus vehicles used for solubilization of derivatives (0.01% Tween) and NB (blank nanoemulsion 880 µg/ml). The in vivo assay was done in 35 quails (Coturnix coturnix) infected experimentally 4x104 mg/kg,  were divided in   seven groups (n=5): A (control-healthy), B (control infected), C (control TW 0.01%), D (NB 0.88 mg/kg), E (drug MTZ 25 mg/kg, F (OE-CL at 0.55 mg/kg ) and G (N-CL at 0.44 mg/kg), during 7 consecutive days. Results: The in vitro test showed that the OE-CL (550 μg/ml) and N-CL (440 μg/ml) concentrations reduced the trophozoites viability in 100%. In the in vivo test, the treatment with OE-CL was efficient on the 4th treatment day and the N-CL after the 3rd day, and the MTZ in the therapeutic concentration was efficient on the 7th day. Conclusion: It can be observed in this study that the lemon grass has natural potential antitrichomonal activity against T. gallinae in vitro and in vivo.